METODE MNEMONIK GURU SEKOLAH DASAR DALAM MENINGKATKAN DAYA INGAT PESERTA DIDIK - Triyanto, Yoel; Saleky Combi, Jemy; Putra Hura, Martin; Laoli, Septiniar (Universitas Islam 45 Bekasi, 2024)
The world of education today, especially at the elementary school level, has a number of hot issues that need attention, related to difficulties in remembering the material that has been learned. It is likely that this issue is caused by a lack of variety in learning, lack of individualised support from educators, learning methods that are not in accordance with the interests of learners, material overload (too much material in 1 learning session), lack of learner involvement, lack of connection and context, and lack of facilities in learning. Teachers are agents of change who have a very important role in shaping and developing the potential of students including in improving students' memory. The purpose of this study is to make a significant contribution in the context of developing effective learning strategies at the primary school level. The practical implications of the findings indicate the importance of the integration of mnemonic methods in the curriculum to support the achievement of learning objectives and improve learners' memory.